Genetic and phenotypic parameter estimates of body weight and egg production traits of Tilili chicken in Ethiopia - Kassa, Birhan; Taye, M.; Esatu, Wondmeneh; Kebede, A.; Girma, Mekonnen; Kebede, F.G.; Banos, G.; Watson, K.; Hanotte, Olivier H.; Dessie, Tadelle (MDPI, 2025)
High genetic variation in African indigenous chicken populations provides opportunities for long-term genetic improvement. This study estimated genetic parameters for economic traits based on data derived from a nucleus flock comprising two generations, derived from 40 sires and 200 dams in a line breeding program through mass selection. Body weight (BW) at different weeks was analyzed for 1370 chickens. Similarly, egg performance was evaluated on 473 hens kept for 44 weeks. Genetic parameters were estimated using a multi-trait animal model based on an average information-restricted maximum likelihood (AI-REML) algorithm in WOMBAT software. Body weight showed significant heritability (p < 0.001), ranging from 0.251 for body weight at 8 weeks of age (BW8) to 0.34 for body weight at 16 weeks of age (BW16), indicating a good genetic improvement potential. Egg production traits had low to moderate heritability (0.08–0.37). Positive genetic correlations among growth traits, particularly BW8 and body weight at 12 weeks of age, BW12 (rG = 0.94), suggest shared genetic influences and the possibility of improving multiple traits simultaneously. The genetic correlation between BW16 and the cumulative egg number varied from low and negative (−0.02) in the first two months to high (0.51) in the cumulative egg number over six months, suggesting that heavier birds lay more eggs over time. Our limited dataset based on two generations and pedigree demonstrates that BW16 with egg production has moderate heritability and strong genetic correlations that can lead to genetic progress toward the development of a dual-purpose breed, and this offers a scientific basis for breeders to develop selection indices to develop a dual-purpose breed for smallholder production systems.